تقييم الإدراك البصري لدى الأطفال المتمدرسين في السنة الأولى ابتدائي - مهول فازية; أزداو شفيقة (University of Eloued جامعة الوادي, 2024)
ملخص: يعتبر الإدراك البصري من العمليات المعرفية الأساسية التي تتدخل في عملية التعلم، وقد أشار الدليل التشخيصي الإحصائي العالمي إلى إمكانية تقييم صعوبات الإدراك البصري في بداية سن التمدرس، لما لها من تأثيرات سلبية على اكتساب المهارات الأكاديمية، وهذا ما دفعنا إلى دراسة إمكانية تشخيص هذه الصعوبات لـدى الأطفال الجزائريين المتمدرسين في السنة أولى ابتدائي، ومعرفة إمكانية الاعتماد في ذلك على اختبار (عبد الحميد سليمان السيد، 2003)، علما أنه قد أعد لتشخيص صعوبات الإدراك البصري لدى أطفال تتراوح أعمارهم ما بين 8 إلى 9 سنوات. يرجع هذا الاختيار رغم عدم تناسب سن العينة، نظرا للتغير الاجتماعي والتقدم التكنولوجي السريع الذي أثر على النمو المعرفي لدى الأطفال في وقتنا الحالي. أكدت النتائج إمكانية الاعتماد على هذا الاختبار كونه يتمتع بخصائص سيكومترية جيدة وله قدرة عالية في التمييز بين ألجيدي والضعاف في الإدراك البصري. Abstract: the study aimed to explore the availability of psychometric properties of a visual perception assessment test developed by El-Sayed (2003), and verify its suitability for evaluating visual perception difficulties among Algerian children studying in the first year of primary school. The test was administered to a sample of 97 schoolchildren from three primary schools in the Tizi Ouzou province during the academic year (2019-2020), and a descriptive approach was used, both correlational and comparative. It’s noteworthy that this test was originally designed to diagnose visual perception difficulties in children aged 8 to 9 years old. Despite the mismatch in the sample age, this choice was made due to rapid social change and technological advancement, which have influenced children’s cognitive development in the current era. The results confirmed the possibility of relying on this test, as it exhibited good psychometric properties and a high ability to distinguish between those with good and weak in visual perception.
البيئة الجزائرية نموذجا
Keywords: تقييم صعوبات الإدراك البصري; الأطفال المتمدرسين; القياس والخصائص السيكومترية; Visual perception difficulties assessment; children studying; measurement and psychometric properties